Relationship between Socio-Demographic Characteristics and Job Satisfaction: Evidence from Private Bank Employees - Rahman, Md. Mostafijur; Chowdhury, Md. Razwan Hasan Khan; Islam, Md. Amirul; Tohfa, Mst. Ummay; Kader, Md. Abdul Latif; Ahmed, Alim Al Ayub; Donepudi, Praveen Kumar (American Journal of Trade and Policy, 2020)
In this competitive business world satisfied employee is the prime asset of any business organization as an employee’s satisfaction can ensure continuous growth. The purpose of this study was to find out, is there any significant relationship between socio-demographic characteristics and job satisfaction of private bank employees in Bangladesh? By using Yamane’s (1967) formula the study consisted of 56 (male 89.3% and female 10.7%) respondents and it used semi-structured questionnaires containing pre-coded and open-ended questions. All questions were rated with the Likert 5-point scale. As all the variables used in this study (both dependent and independent) were categorical, the Chi-square test was used to assess the relationship. In this study, significant relations were found between some demographic characteristics, such as, sex, age, salary, and family income with job satisfaction indicators which were participation in decision making, training facilities, and increase knowledge and capacity. Education and geographic location did not show any significant relationship with job satisfaction indicators. Around 92.5% of male employees reported that the current organization helped to increase their knowledge and working capacity (p<0.028). More than half of the employees (55.3 %) of the 30-35 age group could not take part in decision making (p<0.013). In addition, family income and salary also exerted significant associations with participation in decision-making and proper training facilities respectively. Several stakeholders and concern authorities should give top priority in these demographic areas while developing strategies to improve the job satisfaction level of employees.